Pengaruh Pembelajaran Blended Learning Berbantukan Media Aplikasi Quipper School terhadap Minat, Kemandirian, dan Hasil Belajar pada Materi Gelombang Mekanik Siswa Kelas XI SMA Negeri 1 Cawas - Marini Marini; Dwi Sulisworo; Ishafit Ishafit (Jurnal Penelitian Pembelajaran Fisika, 2017)
The aims of this study are to determine the differences in students’  learning interest, to know the differences in the level of students’ learning independence,  to know the  differences in achievements of cognitive learning outcomes of students who learn conventionally and those who  learn  using  blended learning method. The type of this research is quasi experiment with pretest-posttest controlled group design. Control class learn conventionally while experimental classes learn in blended learning, which is a conventional learning process combined with online learning, by utilizing the application of Quipper school. Students’ learning interest in control class before the learning process gets an average value of 118.74 while after the learning process gets an average value of 123.78. As for the experimental class, before the learning process gets an average value of 119.89 while after the learning process gets an average score of 131.21. For the level of students’ learning independence of the control class during the learning process gets an average score of 28.5 while for the experimental class during the learning process gets an average score of 35.1. So there is a difference of 6.6 between the control class and the experimental class. The students’ cognitive learning outcomes of the control class before the learning process gets an average score of 40.3, while after the learning process gets an average score of 58.67. As for the experimental class, before the learning process gets an average score of 42.29 while after the learning process gets an average score of 76.71. So the increase of control class is 18,37 while experiment class is 34,43.